THE EFFECTS OF PROMOTION MIX ON CUSTOMERS’ BUYING DECISION - Wahyudi, Adrian Ekky A.; Melinda, Tina (Jurnal Entrepreneur dan Entrepreneurship, 2018)
The purpose of the research is to determine the effect of promotion mix, namely, advertising, personal selling, and public relations on buying decision. The population of the research included the consumers of Warung Ndeso Jancuocok. While the numbers of samples using Slovin showed 85.7, the researcher decided to take 89 respondents for this research. Sixteen questions in the questionnaire were used to collect data, weighted by Likert scale. The research was conducted from October to November 2017. This present study used multiple regression analysis and validity – reliability tests. Hypothesis testing was performed using F test, t test, correlation coefficient of determination and partial determination coefficient. The research used classical assumption test such as multicollinearity test, heteroskedastic test, autocorrelation test, normality test and linearity test. This study found that Advertising and Personal Selling had a significant effect on customers’ buying decisions. Meanwhile, public relation variable had no significant effect on customers’ buying decisions.